"I am nature": Understanding the possibilities of currere in curriculum studies and aesthetics. Issue 3 (2nd September 2017) - Slattery, Patrick
ABSTRACT: This article explores a perspective on nature and aesthetics as currere, which is the foundational concept of curriculum theory. Beginning with the statement "I am nature" by Jackson Pollock and moving through works by of Kiefer, Hofmann, and Magritte, this article explores contemporary art theory and connects the notion of synthetical moments in curriculum theory to an integrated understanding of aesthetics. Michel Foucault's dialogues with Rene Magritte on philosophy and art inform understandings of the unconscious to form a vision of nature and self in the aesthetic process. This article reviews significant historical aspects of currere, from Schubert, Pinar, and Grumet in curriculum theory, and relates the development of curriculum theory to Jackson Pollock's abstract expressionism.